Characterisation of Co/Mn catalysts synthesised via reverse microemulsion method - Mohd Zabidi, N.A. (Maney Publishing, 2014)
The objective of this work is to investigate the effects of manganese on the morphology and reducibility of cobalt catalyst. A series of Co/Mn catalyst was prepared via a reverse microemulsion method on a SiO2 support. The metal loading was kept at 10 wt-. The Mn/Co mol ratio was set at 0, 0 05, 0 12 and 0 25. Based on the transmission electron microscopic analyses, the average particle size of the catalyst was found to be in the range of 3-5 nm for the different catalyst formulation. The presence of up to 12 mol- Mn enhanced the reducibility of the Co-based catalyst. The catalytic activity in the Fischer-Tropsch reaction varied with the content of Mn in the Co-based catalyst. The highest CO conversion (20 5) and C5+ selectivity (12 6) were obtained using the 88Co12Mn/SiO2 catalyst. Â© 2014 W. S. Maney & Son Ltd.